Frequency of side effects of sofosbuvir and daclatsavir in patients of chronic Hepatitis C - KhawajaTahirMaqbool,SahrishRashid,ArslanShahzad,SidraRafique, KhawajaTahirMaqbool,SahrishRashid,ArslanShahzad,SidraRafique (Journal of Rawalpindi Medical College, 2019)
Objective: To evaluate side effects of direct acting antivirals for hepatitis C patients. Study Design: Descriptive case series. Setting: Hepatitis Clinic, Medical Unit II, Jinnah Hospital Lahore. Duration Of Study: three months starting from 1st Dec 2018 to 28th Feb 2019. Subjects And Methods: Forty patients meeting the inclusion criteria were included in the study. All patients were then given direct anti-virals for a period of three months. Patients were called after every four weeks and observed for the presence of side effects like fever, fatigue, malaise, generalized weakness, myalgia, nausea and vomiting. Data was entered and analyzed in SPSS version ver.21.0. Frequency and percentages were calculated for demographic and clinical profile and side effects. Mean and Standard deviation was calculated for biochemical values at base line and end of therapy. Chi-square test was used to assess side effects among age, gender and duration of disease and paired t test for biochemical parameters with p < .05 as statistical significance. Results: Mean age of the patients was 39 years + 11.6. Fever was recorded in 72.5% fatigue was seen in 52.5%, malaise was recorded in 37.5% and generalized weakness was noticed in 37.5. Myalgia was recorded in 12.5% and nausea and vomiting were reported in 2.5% of patients. . (p> .05). There was a statistically significant difference between mean baseline and at end treatment values for AST, ALT, AP and TLC. ( P< .05). Conclusion: Our study concluded that along with efficacy advantage of DAA therapy, their safety profile is acceptable in terms of adverse drug reaction of immediate or during treatment however long term follow up is needed to ascertain and apprehend the safety matters linked with the utilization of DAAs. Key Words: Direct acting antivirals (DAAs), side effects, chronic hepatitis C.